The PROMoting the USE of SWATs (PROMETHEUS) programme: Lessons learnt and future developments for SWATs. Issue 4 (September 2022) - Clark, Laura; Arundel, Catherine; Coleman, Elizabeth; Doherty, Laura; Parker, Adwoa; Hewitt, Catherine; Beard, David; Bower, Peter; Brocklehurst, Paul; Cooper, Cindy; Culliford, Lucy; Devane, Declan; et al.
Introduction: The PROMETHEUS programme (PROMoting THE USE of SWATs) was funded by the UK Medical Research Council (MRC) and Clinical Trials Unit (CTU) infrastructure funding from the National Institute for Health Research (NIHR). The purpose was to develop strategies to increase the recruitment and retention evidence base. This paper aims to present observations from this work. Observations: The PROMETHUS programme funded 42 SWATs, the average cost of each SWAT was £4007. A central coordination point enabled a concentrated effort in SWAT research activity leading to a rapid increase in the evidence base. The methodological feasibility of undertaking a coordinated SWAT design was established. The international Trial Forge SWAT Network was developed in 2021 to connect research groups in response for the need to connect teams undertaking methodological research. A SWAT reporting template and a database of researchers willing to peer review SWATs are also needed to improve the reporting of SWATs. Discussion: There is a need to develop a strategy to aid teams to identify a suitable SWAT for their host trial populations and a mechanism to communicate SWAT research priorities. Work is needed to increase the awareness of the methodological importance of SWAT research with research teams and develop engagement strategies to increase SWAT activity. Continued collaboration with the HRA is necessary to refine the SWAT approvals process. Conclusion: The coordination PROMETHEUS provided is crucial to increasing the recruitment retention evidence base. The Trial Forge Network will be key to provide ongoing networking and dissemination opportunities.